Crankshaft failure analysis of a boxer diesel motor. (October 2015) - Fonte, M.; Anes, V.; Duarte, P.; Reis, L.; Freitas, M.
Highlights: Failure mode analysis. Crankshaft failure due to bedplate weakness. Crankshaft failure of a boxer diesel engine. Stress concentration on crankpin-web fillets. Crankshaft failure mechanisms. Abstract: This paper reports a failure mode analysis of a boxer diesel engine crankshaft. Crankshafts are components which experiment severe and complex dynamic loadings due to rotating bending combined with torsion on main journals and alternating bending on crankpins. High level stresses appear on critical areas like web fillets, as well as the effect of centrifugal forces and vibrations. Since the fatigue fracture near the crankpin-web fillet regions is one of the primary failure mechanisms of automotive crankshafts, designers and researchers have done the best for improving its fatigue strength. The present failure has occurred at approximately 2000 manufactured engines, and after about 95, 000 km in service. The aim of this work is to investigate the damage root cause and understand the mechanism which led to the catastrophic failure. Recommendations for improving the engine design are also presented.